2017
DOI: 10.2196/jmir.7428
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Surveys for Collecting Population-Level Estimates in Low- and Middle-Income Countries: A Literature Review

Abstract: BackgroundNational and subnational level surveys are important for monitoring disease burden, prioritizing resource allocation, and evaluating public health policies. As mobile phone access and ownership become more common globally, mobile phone surveys (MPSs) offer an opportunity to supplement traditional public health household surveys.ObjectiveThe objective of this study was to systematically review the current landscape of MPSs to collect population-level estimates in low- and middle-income countries (LMIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
142
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 58 publications
3
142
0
1
Order By: Relevance
“…These surveys include interactive voice response (IVR), where a participant uses a mobile phone keypad to enter responses to a prerecorded and automated questionnaire. IVR surveys have been used to collect subnational13 14 and national estimates15 of health and demographic indicators in LMICs. However, optimal implementation of MPS in these contexts remains poorly understood, particularly in regard to increasing participation rates and ensuring equitable data collection from different population segments 16.…”
Section: Introductionmentioning
confidence: 99%
“…These surveys include interactive voice response (IVR), where a participant uses a mobile phone keypad to enter responses to a prerecorded and automated questionnaire. IVR surveys have been used to collect subnational13 14 and national estimates15 of health and demographic indicators in LMICs. However, optimal implementation of MPS in these contexts remains poorly understood, particularly in regard to increasing participation rates and ensuring equitable data collection from different population segments 16.…”
Section: Introductionmentioning
confidence: 99%
“…Active monitoring, the focus of our present work, requires deliberate participation of patients, communities, and/or health workers in reporting health information. Traditionally, active public health surveillance has been carried out through face-to-face (F2F) household surveys or contact with health care providers which can be considerably time and resource intensive (Gibson et al, 2017). The increasing ubiquity of mobile phone devices and availability of phone survey platforms provide an opportunity to explore the use of mobile phone surveys (MPS) to support active disease and risk factor surveillance, including for non-communicable diseases (NCDs) (Brinkel, Krämer, Krumkamp, May, & Fobil, 2014;Hyder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative that would be more accurate is to directly observe health workers over time to record ISA indicators, which would be prohibitively time and resource-intensive. While several studies have shown that using mobile phone interviews for data collection provided accurate results at cheaper costs, further research should be conducted to explore whether respondents are more likely to give socially desirable responses over the phone, even when questions are about fairly objective attributes measuring structural quality [23,25].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing saturation of mobile phones among the population in SSA countries makes use of mobile phones a viable alternative to collecting data through costly field work [24]. Still, using mobile phones for data collection has its own set of challenges, such as network availability and desirability bias among respondents [23,25].…”
Section: Introductionmentioning
confidence: 99%